Column [5] arene organic polymer material as well as preparation method and application thereof
The column [5] aromatic organic polymer prepared by Friedel-Crafts polymerization solves the problem of limited iodine adsorption capacity in the prior art, and realizes efficient adsorption and separation of iodine, which has important practical application value.
Patent Information
- Application Number
- CN202411867111.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems in iodine adsorption with limited adsorption capacity, limited number of adsorption sites, and slow adsorption rate, resulting in limited widespread application in practical applications.
Column [5] aromatic organic polymers were prepared by Friedel-Crafts polymerization. The synthesis body was made of column [5] aromatic hydrocarbons, organic polymer materials with the same crosslinking agent but different proportions were used for the separation and recovery of iodine ions and iodine steam.
实现了对碘的优异吸附能力,制备成本低、稳定性高,为分离和回收碘提供了新的思路,具有重要的实际意义。
Smart Images

Figure CN119661793A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of iodine separation and recovery, and in particular to a columnar aromatic organic polymer material and a preparation method and application thereof. Background Art
[0002] Nuclear power plants and nuclear weapons are sources of considerable concern because of the large amounts of radioactive pollutants they produce. An example of radioactive waste produced by nuclear fission in a power plant is the isotope 129 I and 131 I. Among these isotopes, 129 I is of particular concern because of its long half-life, lasting approximately 1.57 × 10 7 Year. 129 The continued presence of I in the environment raises concerns about its effects on human health. Therefore, radioactive iodine must be captured and stored safely before it causes harm.
[0003] Incorporating supramolecular macrocycles and supramolecular interactions into materials can endow them with remarkable functions. Macrocyclic molecules, especially those with complementary binding groups, have been used to construct porous materials because they often endow these materials with unexpected properties. For example, Sankar Srividhya et al. synthesized porous organic polymers using pillar[5]arene and a crosslinker through FC reaction, which can adsorb iodine vapor and iodine ions in aqueous iodine solution. It has various adsorption sites for the effective removal of iodine and organic micropollutants. Therefore, macrocyclic organic polymers have good application prospects in the field of iodine ion and iodine vapor adsorption.
[0004] Pillarene has an electron-rich rigid ring and oxygen atoms, and can be easily functionalized by changing the substituents on the benzene ring, providing valuable properties for the removal or detection of pollutants. Due to its electron-rich properties, pillararene-based materials can also be used to capture iodine. For example, Li et al. synthesized four pillar[5]arene organic polymer materials with pillar[5]arene as the main body and the same cross-linking agent but different proportions, and further used them for the separation of iodine ions and iodine vapor, showing significant separation capabilities. Pillararene-based adsorbents still have great development potential in the field of iodine ion and iodine vapor adsorption.
[0005] Solid adsorbents such as activated carbon (AC) and zeolite have been used as solid adsorbents to capture and store iodine since the early 21st century. However, limited adsorption capacity, a limited number of adsorption sites, and slow adsorption rates have hampered their widespread use in practical applications.
[0006] Therefore, providing an iodine adsorption material with simple process, no pollution to the environment, and strong stability during the adsorption process is a technical problem that urgently needs to be solved. Summary of the invention
[0007] The purpose of the present invention is to provide a pillar[5] aromatic organic polymer material and its preparation method and application to solve the problems existing in the above-mentioned prior art.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] The present invention provides a pillar[5]arene organic polymer obtained by polymerizing an organic polymer unit A and an organic polymer unit B; the organic polymer unit A is:
[0010]
[0011] The organic polymer unit B is:
[0012]
[0013] The connection point between the organic polymerization unit A and the organic polymerization unit B is the No. 2 position of the benzene ring in the organic polymerization unit A.
[0014] The present invention also provides a method for preparing the above-mentioned column [5] aromatic hydrocarbon organic polymer, comprising the following steps:
[0015] The pillar[5]arene is polymerized with dibromobenzophenone in the presence of a catalyst at 80-90° C. for 22 hours to obtain the pillar[5]arene organic polymer.
[0016] Furthermore, the structure of the pillar[5]arene is as follows:
[0017]
[0018] Furthermore, the catalyst is ferric chloride.
[0019] Furthermore, the solvent of the polymerization reaction is ethylene dichloride.
[0020] Furthermore, the molar ratio of the pillar [5] aromatic hydrocarbon to dibromobenzophenone is 1:5-15.
[0021] Furthermore, when the molar ratio of pillar[5]arene to dibromobenzophenone is 1:5, the pillar[5]arene organic polymer having the structure of formula I is mainly obtained:
[0022]
[0023] When the molar ratio of pillar[5]arene to dibromobenzophenone is 1:10, the pillar[5]arene organic polymer having the structure of formula II is mainly obtained:
[0024]
[0025] When the molar ratio of pillar[5]arene to dibromobenzophenone is 1:15, the pillar[5]arene organic polymer having the structure of formula III is mainly obtained:
[0026]
[0027] Furthermore, before the polymerization reaction, the mixed system is stirred at 50-55° C. for 2 hours.
[0028] The invention uses pillar[5]arene and dibromobenzophenone as organic units and prepares pillar[5]arene organic polymer through Friedel-Crafts polymerization reaction.
[0029] The present invention further provides the use of the above-mentioned pillar [5] aromatic organic polymer as an iodine adsorption material.
[0030] The present invention further provides the use of the above-mentioned pillar [5] aromatic organic polymer as a radioactive iodine adsorption material.
[0031] The present invention discloses the following technical effects:
[0032] The present invention provides a columnar[5]arene organic polymer material. Based on the property that columnar aromatics have electron-rich rigid rings and oxygen atoms, a columnar[5]arene organic polymer material is synthesized, wherein the main component is columnar[5]arene and the cross-linking agent is the same but in different proportions, and the material is further used for the separation and recovery of iodine ions and iodine vapor.
[0033] The column [5] aromatic organic polymer material provided by the present invention has low preparation cost and high stability, and has excellent adsorption capacity for iodine, thus providing a new idea for separating and recovering iodine and having important practical significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 The iodine vapor adsorption capacity diagram of the four materials BM-DM prepared in Comparative Example 1 of the present invention and BM-PA1, BM-PA2, and BM-PA3 prepared in Examples 3-5, wherein (a) is BM-DM prepared in Comparative Example 1, (b) is BM-PA1 prepared in Example 3, (c) is BM-PA2 prepared in Example 4, and (d) is BM-PA3 prepared in Example 5;
[0036] Figure 2This is a graph showing the maximum adsorption capacity of BM-DM prepared in Comparative Example 1 of the present invention for aqueous iodine solution;
[0037] Figure 3 This is a graph showing the maximum adsorption capacity of BM-PA1 prepared in Example 3 of the present invention for iodine aqueous solution;
[0038] Figure 4 This is a graph showing the maximum adsorption capacity of BM-PA2 prepared in Example 4 of the present invention for iodine aqueous solution;
[0039] Figure 5 This is a graph showing the maximum adsorption capacity of BM-PA3 prepared in Example 5 of the present invention for aqueous iodine solution;
[0040] Figure 6 This is a physical picture of the adsorption of iodine aqueous solution by BM-PA1 prepared in Example 3 of the present invention;
[0041] Figure 7 This is a physical picture of the adsorption of iodine aqueous solution by BM-PA2 prepared in Example 4 of the present invention;
[0042] Figure 8 This is a physical picture of the adsorption of iodine aqueous solution by BM-PA3 prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0044] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0045] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0047] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0048] Example 1 Preparation of Column [5] Aromatics
[0049]
[0050] Paraformaldehyde (0.93 g, 30 mmol) was added to a solution of 1,4-dimethoxybenzene (1.38 g, 10 mmol) in 1,2-dichloroethane (20 mL), and then diethyl boron trifluoride [BF3O(C2H5)2, 1.25 mL, 10 mmol] was added and stirred at 30°C for 30 min. The solution was poured into methanol and the resulting precipitate was collected by filtration. Recrystallization was performed with chloroform / acetone (1:1 v / v) to obtain 0.83 g of column [5] aromatics (yield: 71%).
[0051] Example 2 Preparation of dibromobenzophenone
[0052]
[0053] 4,4'-Dimethylbenzophenone (5g, 23.78mmol), N-bromosuccinimide (NBS) (9.31g, 52.31mmol) and 2,2'-azobisisobutyronitrile (39mg, 237.79μmol) were added to 100mL CCl4, and the mixture was stirred under N2 and then refluxed for 12h. The mixture was poured into ice water, then extracted with dichloromethane and dried. The organic phases were combined and the solvent was removed. The crude product was used directly in the next reaction. All crude products, 2,5-dimethoxyphenylboronic acid (12.98g, 71.32mmol), Pd(OAc)2 (266.86mg, 1.19mmol), PPh3 (623.53mg, 2.38mmol) and K3PO4 (25.23g, 118.87mmol) were added to a 500mL reaction bottle. Under N2 atmosphere, 100 mL of toluene was added to the mixture, the temperature was raised to 80°C, the reaction was continued for 12 h, the mixture was poured into water, then extracted with dichloromethane and dried, the organic phases were combined, and the solvent was removed. Pure dibromobenzophenone (5.2 g, yield = 45%) was obtained by silica gel column chromatography.
[0054] Example 3 Column [5] Preparation of aromatic polymer BM-PA1
[0055]
[0056] Anhydrous ferric chloride (5 mmol) was added to a mixture solution of column [5] arene (1 mmol) and dibromobenzophenone (5 mmol), and the resulting mixture was added to 40 mL of DCE. The reaction mixture was stirred at 55 °C for 2 hours and then heated at 85 °C for 22 hours. Friedel-Crafts polymerized column [5] arene and dibromobenzophenone to form a dark green precipitate, which was filtered and washed with chloroform to remove unreacted column [5] arene and dibromobenzophenone crosslinker. The residue was then washed with methanol to remove the ferric chloride catalyst. The polymer was further purified by extraction with DCM and methanol for 72 hours respectively, and dried at 100 °C overnight to obtain an organic polymer (brown solid) with BM-PA1 as the main product.
[0057] Example 4 Column [5] Preparation of aromatic polymer BM-PA2
[0058]
[0059] Anhydrous ferric chloride (10 mmol) was added to a mixture solution of column [5] arene (1 mmol) and dibromobenzophenone (10 mmol), and the resulting mixture was added to 40 mL of DCE. The reaction mixture was stirred at 55 °C for 2 hours and then heated at 85 °C for 22 hours. Friedel-Crafts polymerized column [5] arene and dibromobenzophenone to form a dark green precipitate, which was filtered and washed with chloroform to remove unreacted column [5] arene and dibromobenzophenone crosslinker. The residue was then washed with methanol to remove the ferric chloride catalyst. The polymer was further purified by extraction with DCM and methanol for 72 hours respectively. Drying at 100 °C overnight gave an organic polymer (brown solid) with BM-PA2 as the main product.
[0060] Example 5 Column [5] Preparation of aromatic polymer BM-PA3
[0061]
[0062] Anhydrous ferric chloride (15 mmol) was added to a mixture solution of column [5] arene (1 mmol) and dibromobenzophenone (15 mmol), and the resulting mixture was added to 40 mL of DCE. The reaction mixture was stirred at 55 °C for 2 hours and then heated at 85 °C for 22 hours. Friedel-Crafts polymerized column [5] arene and dibromobenzophenone to form a dark green precipitate, which was filtered and washed with chloroform to remove unreacted column [5] arene and dibromobenzophenone crosslinker. The residue was then washed with methanol to remove the ferric chloride catalyst. The polymer was further purified by extraction with DCM and methanol for 72 hours respectively. Drying at 100 °C overnight gave an organic polymer (brown solid) with BM-PA3 as the main product.
[0063] Comparative Example 1 Preparation of polymer BM-DM
[0064]
[0065] Anhydrous ferric chloride (10 mmol) was added to a mixture solution of dimethoxybenzene (1 mmol) and dibromobenzophenone (10 mmol), and the resulting mixture was added to 40 mL of DCE. The reaction mixture was stirred at 55 ° C for 2 hours and then heated at 85 ° C for 22 hours. Friedel-Crafts polymerized dimethoxybenzene and dibromobenzophenone to form a dark green precipitate, which was filtered and washed with chloroform to remove unreacted dimethoxybenzene and dibromobenzophenone crosslinkers. The residue was then washed with methanol to remove the ferric chloride catalyst. The polymer was further purified by extraction with DCM and methanol for 72 hours, and dried overnight at 100 ° C to obtain BM-DM (brown solid).
[0066] Effect verification example:
[0067] 1. Iodine vapor adsorption test
[0068] A known mass of polymer is placed in a glass vial which is then placed in a sealed glass bottle containing a large excess of iodine pellets. The entire setup is placed in a preheated oven at 75°C. The weight of the sample is monitored at various time intervals.
[0069] Static I2 vapor absorption at a certain time (q t , g·g -1 ) is calculated using the following formula:
[0070]
[0071] Where: q t Indicates I2 adsorption capacity, unit: g·g -1 ; m0 represents the mass of the polymer before I2 adsorption, unit: g; mt It represents the mass of polymer after I2 adsorption, in g.
[0072] The iodine vapor adsorption capacity of BM-DM prepared in Comparative Example 1 and BM-PA1, BM-PA2, and BM-PA3 prepared in Examples 3-5 is as follows: Figure 1 As shown in the figure, the maximum adsorption capacity of iodine vapor of the four materials BM-DM, BM-PA1, BM-PA2 and BM-PA3 is 1.57 g / cm2, respectively. -1 , 2.26gg -1 , 2.41gg -1 and 2.38gg -1 .
[0073] 2. Iodine solution adsorption test:
[0074] An appropriate amount of elemental iodine and potassium iodide were dissolved in deionized water to prepare aqueous iodine solutions containing different concentrations of 50-500 mg / L. The adsorption capacity of the four materials under different concentrations of iodine ions was tested to determine the maximum adsorption capacity of these materials for iodine.
[0075] 10 mg of BM-DM prepared in Comparative Example 1 and BM-PA1, BM-PA2, and BM-PA3 prepared in Examples 3-5 were taken as adsorbents and added to 50 ml of iodine aqueous solution of different concentrations, and then shaken at 240 rpm and 25° C. Finally, the aqueous phase was separated by a 0.22 mm membrane syringe filter, and the initial concentration and equilibrium concentration of iodine were determined by a UV spectrophotometer.
[0076] The adsorption amount of iodine (q e , mg.g -1 ) is calculated as follows:
[0077]
[0078] In the formula, C0 (mg·L -1 ) is the initial concentration, C e (mg·L -1 ) is the equilibrium concentration, V(L) is the volume of the solution, and m(g) is the weight of the adsorbent.
[0079] Figure 2-Figure 5The maximum adsorption capacity of BM-DM prepared in comparative example 1 and BM-PA1, BM-PA2, and BM-PA3 prepared in examples 3-5 for aqueous iodine solution is shown in the figure. It can be seen that the maximum adsorption capacity of BM-DM, BM-PA1, BM-PA2, and BM-PA3 for iodine is 224.64 mg / g, 604.1 mg / g, 863.76 mg / g, and 594 mg / g, respectively, and the polymer material prepared by the present invention has significantly excellent adsorption performance for iodine solution.
[0080] Figure 6-Figure 8 The actual pictures of the adsorption test of 80mg / L iodine solution by four materials BM-PA1, BM-PA2 and BM-PA3 prepared in Examples 3-5 are shown in Figure 3. The adsorption test was sampled every 5 minutes. BM-PA1 reached the maximum adsorption at 45 minutes, BM-PA2 reached the maximum adsorption at 40 minutes, and BM-PA3 reached the maximum adsorption at 30 minutes.
[0081] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A pillar[5]arene organic polymer, characterized in that Obtained by polymerization of organic polymerization unit A and organic polymerization unit B; the organic polymerization unit A is: The organic polymer unit B is:
2. The method for preparing the pillar [5] aromatic organic polymer according to claim 1, characterized in that: The following steps are involved: The pillar[5]arene is polymerized with dibromobenzophenone in the presence of a catalyst at 80-90° C. for 22 hours to obtain the pillar[5]arene organic polymer.
3. The preparation method according to claim 2, characterized in that: The catalyst is ferric chloride.
4. The preparation method according to claim 2, characterized in that: The solvent for the polymerization reaction is ethylene dichloride.
5. The preparation method according to claim 2, characterized in that: The molar ratio of the pillar [5] aromatic hydrocarbon to dibromobenzophenone is 1:5-15.
6. The preparation method according to claim 2, characterized in that: Before the polymerization reaction, the method further comprises stirring the mixed system at 50-55°C.
7. Use of the column [5] aromatic organic polymer as claimed in claim 1 as an iodine adsorption material.
8. Use of the column [5] aromatic organic polymer as claimed in claim 1 as a radioactive iodine adsorption material.
Citation Information
Patent Citations
Large-aperture triindolyl alkyl porous compound as well as preparation method and application thereof
CN115028811A